Learn From The Biggest Accounting Fraud In 95 Years - Shinta Maharani; Asmak Ab Rahman; Veni Soraya Dewi (Jurnal Analisis Bisnis Ekonomi, 2023)
This study analyses the panel data on the 96 most significant fraud cases from 1925 to 2020. The focus will be on agency theory because it affects falsified accounting as the most common type of accounting fraud and then Overstated Assets, Sales, and Revenues. Descriptive statistics with the 96 most prominent cases based on literature have been identified to understand the topic better. The data collected from 1925 to 2020 is presented and summarised in specific tables and graphs for a more immediate understanding. The mixed method was used to analyze 476 data items, both quantitative and qualitative research, with SPSS and Nvivo applications. This research found that 61 out of 96 fraud cases are from the USA, and the most auditor firm being Price Water House. The evidence that emerged is that none of the cases analyzed deals with the pandemic --the fraud occurred years ago- to understand possible practical implications and further theoretical contributions. This research suggests that auditors should apply business ethics to be more proactive and pragmatic, considering how quickly events change and the uncertainty that arises. This study contributes to advancing knowledge of the accounting world, specifically of fraud. As far as the authors know, this is the first study that analyzes the panel data on fraud with mixed methods.